2020
DOI: 10.1016/j.scitotenv.2020.137803
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of UV filters on marine bacteria: Combined effects with damaging solar radiation

Abstract: Five organic UV filters were tested for the first time on 27 marine bacteria. • Seven bacteria demonstrated sensitivity against at least one UV filter. • Octinoxate is the most toxic UV filter, affecting 5 out of 7 sensitive species. • The physiological state plays a key role in the bacterial sensitivity to UV-filters. • Solar radiation modulates UV filters toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 67 publications
1
14
0
2
Order By: Relevance
“…Genomes of bacterial species screened for sensitivity 16 were downloaded from NCBI (https://www.ncbi.nlm.nih.gov/genome). The following strains were selected: Paenibacillus glucanolyticus NBRC 15330, Bacillus megaterium ATCC 14581, Halobacillus dabanensis CGMCC 1.3704, Algoriphagus ornithinivorans DSM 15282, and Algoriphagus mannitolivorans DSM 15301.…”
Section: Bacterial Strain Genomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Genomes of bacterial species screened for sensitivity 16 were downloaded from NCBI (https://www.ncbi.nlm.nih.gov/genome). The following strains were selected: Paenibacillus glucanolyticus NBRC 15330, Bacillus megaterium ATCC 14581, Halobacillus dabanensis CGMCC 1.3704, Algoriphagus ornithinivorans DSM 15282, and Algoriphagus mannitolivorans DSM 15301.…”
Section: Bacterial Strain Genomesmentioning
confidence: 99%
“…Bacteria are an interesting ecotoxicological model as they are easy to handle, constitute a major part of the marine biomass 17 , and support essential function in marine ecosystems 18 . In a former study, marine bacteria from the major phyla, namely Actinobacteria, Bacteroidetes, Firmicutes, and Proteobacteria, were sensitive to UV lters from 200 µg/L 16 . Environmentally relevant bacteria investigated in this study belong to the Bacteroidetes, the most abundant phyla after Proteobacteria in marine environments 19 , and the Firmicutes, widespread symbionts in marine organisms 20,21 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This phototoxicity, which is considered as a major contributor of bacterial die-off in the marine ecosystem (Lozano et al, 2020;Zaafrane & Maatouk, 2012), is the result of reactive oxygen species (ROS) such as superoxide, hydrogen peroxide, and hydroxyl radical generated by a natural or an artificial photosynthesizers when they are exposed to sunlight radiations (Imlay, 2019;Zinser, 2018). The ROS action has been recognized as an important factor causing DNA, protein, and lipid alteration and ultimately causes bacteria death (Ezraty et al, 2017;Hong et al, 2019;Matallana-Surget & Wattiez, 2013;McClary & Boehm, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Their bioaccumulation, biomagnification ( Lozano et al, 2020a ) and their occurrence were reported in freshwater and marine environments from the surface microlayer ( Fagervold et al, 2019 ), water column ( Langford et al, 2015 ; Sánchez Rodríguez, Rodrigo Sanz & Betancort Rodríguez, 2015 ) to sediments ( Apel, Joerss & Ebinghaus, 2018 ; Ramos et al, 2015 ). UV filters toxicity was demonstrated on a broad range of organisms ( Barone et al, 2019 ; Danovaro et al, 2008 ; Downs et al, 2016 ; He et al, 2019 ; Seoane et al, 2017 ; Stien et al, 2021 ; Ziarrusta et al, 2018 ), including bacteria ( Lozano et al, 2020b ), yet UV filters toxicity mechanisms remain unclear. Bacteria are an interesting ecotoxicological model as they are easy to handle, constitute a major part of the marine biomass ( Bar-On, Phillips & Milo, 2018 ), and support essential function in marine ecosystems ( Yilmaz et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%